Hubungan pembangunan industri pelancongan dan pertumbuhan ekonomi di beberapa negara utama ASEAN - Othman, Redzuan; Mohd Salleh, Norlida Hanim (Universiti Utara Malaysia, 2010)
Purpose - This study investigated the pattern of relationship between the development of tourism industry and the economic growth in major ASEAN countries namely Malaysia, Thailand, Singapore, and Indonesia. More specifically,this study tested hypotheses whether tourism development is a cause for economic growth (tourism-led economic growth – TLG) or the economic growth is a cause for tourism development (economic growth led tourism – GLT). Design/Methodology/Approach - An econometric analysis which applied the cointegration test and Granger causality analysis was employed to clarify these issues. Findings - Results of the study had shown that there is only a one-way relationship between tourism development and economic growth in these countries. For Thailand and Indonesia economic growth is the leading factor for tourism development (GLT) whereas in Malaysia and Singapore, tourism development is the leading factor for economic growth (TLG).Originality/Value - This paper investigate whether tourism-led economic growth – TLG) or the economic growth led tourism development– GLT). It is important especially for the policy makers since it can give some ideas to further develop economic growth as well as the tourism industry.